2021
DOI: 10.1177/23328584211008105
|View full text |Cite
|
Sign up to set email alerts
|

Student Learning in Online College Programs

Abstract: We draw on administrative data from the country of Colombia to assess differences in student learning in online and traditional on-campus college programs. The Colombian context is uniquely suited to study this topic, as students take a compulsory exit examination at the end of their studies. We can therefore directly compare the performance on the exit exam for students in online and on-campus programs both across and within institutions, degrees, and majors. Using inverse probability weighting methods based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
9
0
1
Order By: Relevance
“…Germany (Williyan, 2020) 3. Language Learning & Technology USA (Cellini, & Grueso, 2021) 4. AERA Open USA (Nieuwoudt, 2020) 5.…”
Section: Npj Science Of Learningmentioning
confidence: 99%
“…Germany (Williyan, 2020) 3. Language Learning & Technology USA (Cellini, & Grueso, 2021) 4. AERA Open USA (Nieuwoudt, 2020) 5.…”
Section: Npj Science Of Learningmentioning
confidence: 99%
“…Recent studies have shown that synchronous online teaching through virtual classrooms provide better outcomes for student learning than asynchronous classes (Cellini & Grueso, 2021). This method of instruction enabled by new technology has brought online instruction one step closer to in-person instruction in a way that was not possible before.…”
Section: Hope Of Post-pandemic Datamentioning
confidence: 99%
“…By construing the psychosocial needs of students as individual mental health issues, institutions avoid the responsibility of building positive ecosystems. Yet, with local stigma around help-seeking and poorly resourced mental health services [19,20], alongside post-COVID learning losses and weak performance on university exams more generally [21,22], and ongoing future economic and employment uncertainty, learning institutions must and can do more [2,3,[23][24][25]. Further, as many countries are now focused on wellbeing as a national priority, as is the case in the United Arab Emirates (UAE) where this study is situated, educational institutions have additional incentive to meet this national aim, although universities have been slow to adopt the view that wellbeing matters.…”
Section: Introductionmentioning
confidence: 99%